Decoupled Solar Energy Storage and Dark Photocatalysis in a 3D Metal–Organic Framework. Issue 1 (14th November 2022) - Stanley, Philip M.; Sixt, Florian; Warnan, Julien
Abstract: Materials enabling solar energy conversion and long‐term storage for readily available electrical and chemical energy are key for off‐grid energy distribution. Herein, the specific confinement of a rhenium coordination complex in a metal–organic framework (MOF) unlocks a unique electron accumulating property under visible‐light irradiation. About 15 C gMOF −1 of electric charges can be concentrated and stored for over four weeks without loss. Decoupled, on‐demand discharge for electrochemical reactions and H2 evolution catalysis is shown and light‐driven recharging can be conducted for >10 cycles with ≈90% of the initial charging capacity retained. Experimental investigations and theoretical calculations link electron trapping to MOF‐induced geometry constraints as well as the coordination environment of the Re‐center, highlighting the key role of MOF confinement on molecular guests. This study serves as the seminal report on 3D porous colloids achieving photoaccumulation of long‐lived electrons, unlocking dark photocatalysis, and a path toward solar capacitor and solar battery systems. Abstract : A material is showcased that combines light harvesting, photoinduced free‐electron generation, and long‐lived electron storage over several weeks. This phenomenon arises from the geometry‐constraining confinement of a rhenium coordination complex in a metal–organic framework. Decoupled, on‐demand discharge for dark photocatalysis and light‐driven multicycle recharging is demonstrated, highlighting a candidate material toward solar capacitor and solar battery systems.